2020
DOI: 10.1186/s12933-020-01040-5
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin prevents doxorubicin-induced myocardial dysfunction

Abstract: Background Empagliflozin showed efficacy in controlling glycaemia, leading to reductions in HbA1c levels, weight loss and blood pressure, compared to standard treatment. Moreover, the EMPA-REG OUTCOME trial demonstrated a 14% reduction of major adverse cardiovascular events (MACE), a 38% reduction in cardiovascular (CV) death and a 35% reduction in the hospitalization rate for heart failure (HF). These beneficial effect on HF were apparently independent from glucose control. However, no mechanistic in vivo stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 53 publications
5
62
1
1
Order By: Relevance
“…Different mechanisms of [Na + ] lowering seem plausible: SGLT-2 inhibitors have been demonstrated to inhibit the Na + /H + exchanger in murine cardiomyocytes [ 32 ]. Indeed, our results confirm not only the debated presence of SGLT-2 in the LA [ 11 ] but also support the notion of altered cytosolic [Na + ] and [Ca 2+ ] by its inhibition. Work by Lambert et al .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Different mechanisms of [Na + ] lowering seem plausible: SGLT-2 inhibitors have been demonstrated to inhibit the Na + /H + exchanger in murine cardiomyocytes [ 32 ]. Indeed, our results confirm not only the debated presence of SGLT-2 in the LA [ 11 ] but also support the notion of altered cytosolic [Na + ] and [Ca 2+ ] by its inhibition. Work by Lambert et al .…”
Section: Discussionsupporting
confidence: 88%
“…Different mechanisms of [Na + ] lowering seem plausible: SGLT-2 inhibitors have been demonstrated to inhibit the Na + /H + exchanger in murine cardiomyocytes [32]. Indeed, our results confirm not only the debated presence of SGLT-2 in the LA [11] but also support the notion of altered cytosolic [Na + ] and [Ca 2+ ] by its inhibition. Work by Lambert et al indicates a contribution of the SGLT-1 transporter to cytosolic [Na + ] in failing hearts, in particular in the presence of metabolic dysfunction (T2DM, obesity), making it another plausible site-of-action [14].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Same studies indicated that human and murine cardiomyocytes express SGLT-2 [30]. To con rm this data, we analysed SGLT-2 expression in cardiomyocytes and heart tissue of mice.…”
Section: Sglt-2 Expression Through Western Blot Analysismentioning
confidence: 76%
“…Our data con rm that empagli ozin treatment reduces HOMA-IR, as described previously [23], which would improve insulin resistance. In line with a bene cial effect of empagli ozin, the drug has recently been reported to protect the heart from in ammation and energy depletion via AMPK activation [24], as well as preventing doxorubicin-induced myocardial dysfunction [25].…”
Section: Discussionmentioning
confidence: 91%